Walking Without Awareness - Harms, Ilse M.; van Dijken, Joke H.; Brookhuis, Karel A.; de Waard, Dick (Frontiers in Psychology, 2019)
Pedestrians are commonly engaged in other activities while walking. The current study assesses (1) whether pedestrians are sufficiently aware of their surroundings to successfully negotiate obstacles in a city, and (2) whether various common walking practices affect awareness of obstacles and, or, avoidance behavior. To this end, an obstacle, i.e., a signboard was placed on a pavement in the city centre of Utrecht, the Netherlands. The behavioral measure consisted of the distance to the signboard before pedestrians moved to avoid it. After passing, participants were interviewed to obtain thought samples, self-reported route familiarity, a confirmation of secondary task engagement, and to assess awareness through recall and recognition of the signboard and its text. In this study 234 pedestrians participated. More than half of the participants (53.8%) was unaware of the signboard, still none of them had bumped into it. Mind wandering, being engaged in secondary tasks such as talking with a companion or using a mobile phone, and being familiar with a route, did not affect awareness nor avoidance behavior. In conclusion, despite being very common there was no evidence that walking without awareness necessarily results in risk. The absence of awareness does not imply any absence of cognitive and perceptual processing. Pedestrians are still capable of successfully avoiding obstacles in their path, even in visually more challenging environments such as a city centre. It is argued that this is because walking consists of highly automated, skilled behavior.